2017
DOI: 10.3413/nukmed-0833-16-06
|View full text |Cite
|
Sign up to set email alerts
|

Detection of obstructive uropathy and assessment of differential renal function using two functional magnetic resonance urography tools

Abstract: fMRU accurately excluded fixed OU in infants and children, independent from the software used for quantification. However, assessment of DRF with fMRU deviated from DRS especially in infants who may profit most from early intervention. Thus, fMRU cannot fully replace DRS as primary functional examination. If, for clinical reasons, fMRU is performed in first place and it cannot exclude fixed OU, it should be followed by DRS for validation and DRF quantification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
1
6
2
2
Order By: Relevance
“…The use of functional MR urography in determining kidney volume is already accepted as the gold standard in clinical practice regarding complex anatomy architecture cases such as autosomal dominant polycystic kidney disease (31,32). Contrary to recently reported results (21), we found that the absolute difference in volumetric SRF between functional MR urography and DRS did not exceed the accepted tolerance threshold of 5%. The major difference between the protocol adopted in this study and the one from other groups (21,33) is the time and modality of furosemide and Gadolinium-based Contrast Agents administration: while we use the F-0 technique and a micro-bolus of Gadoliniumbased Contrast Agents (7) injection at higher flow rate, other groups adopt the F-15 method (34) with slow Gadoliniumbased Contrast Agents injection.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The use of functional MR urography in determining kidney volume is already accepted as the gold standard in clinical practice regarding complex anatomy architecture cases such as autosomal dominant polycystic kidney disease (31,32). Contrary to recently reported results (21), we found that the absolute difference in volumetric SRF between functional MR urography and DRS did not exceed the accepted tolerance threshold of 5%. The major difference between the protocol adopted in this study and the one from other groups (21,33) is the time and modality of furosemide and Gadolinium-based Contrast Agents administration: while we use the F-0 technique and a micro-bolus of Gadoliniumbased Contrast Agents (7) injection at higher flow rate, other groups adopt the F-15 method (34) with slow Gadoliniumbased Contrast Agents injection.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to recently reported results (21), we found that the absolute difference in volumetric SRF between functional MR urography and DRS did not exceed the accepted tolerance threshold of 5%. The major difference between the protocol adopted in this study and the one from other groups (21,33) is the time and modality of furosemide and Gadolinium-based Contrast Agents administration: while we use the F-0 technique and a micro-bolus of Gadoliniumbased Contrast Agents (7) injection at higher flow rate, other groups adopt the F-15 method (34) with slow Gadoliniumbased Contrast Agents injection. We suppose that the use of ImageJ MRU plug-in protocol associated with the original method of F-0 technique has better correlation with volumetric SRF calculated by DRS and this may explain differences from previous reported data.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Percutaneous nephrostomy and internal stent are equally effec-tive. The inner stent is less effective in the ureteral obstruction, with a high chance of failure, especially in malignant and metastatic disease, chemotherapy, radiotherapy, and kidney failure; therefore, nephrostomy is a more appropriate option (5,6). In cases with coagulation disorder, ureteral stenosis is preferred.…”
Section: Introductionmentioning
confidence: 99%